STUDIES ON THE BIOLOGY OF OPISTHOPTERUS TARDOORE (CVWIER) FROM RATNAGIRI - Desai, S S (Indian Journal of Fisheries, 2011)
The present study deals with the biology of Opisthopterus tardoore (Cuvier)from Ratnagiri. The average growth rate of the fish is 15 mm per month andthe fishery is mainly supported by 0-year group. The fish exhibits carcinivoroustendency and the main food items are Acetes (in case of adults) and copepods(in case of juveniles). The spawning season is from late September to Aprilin which the individual fish spawns twice. The minimum size at first maturityappears to be 116 to 120 mm standard length. The fecundity varies from 1,985to 11,140 depending on the size of the fish